Impact of public health team engagement in alcohol licensing on health and crime outcomes in England and Scotland: A comparative timeseries study between 2012 and 2019 - Frank de Vocht; Cheryl McQuire; Claire Ferraro; Philippa Williams; Madeleine Henney; Colin Angus; Matt Egan; Andrea Mohan; Richard Purves; Nason Maani; Niamh Shortt; Laura Mahon; et al. (Elsevier, 2022)
Summary: Background: Public health teams (PHTs) in England and Scotland engage to varying degrees in local alcohol licensing systems to try to reduce alcohol-related harms. No previous quantitative evidence is available on the effectiveness of this engagement. We aimed to quantify the effects of PHT engagement in alcohol licensing on selected health and crime outcomes. Methods: 39 PHTs in England (n = 27) and Scotland (n = 12) were recruited (of 40 contacted) for diversity in licensing engagement level and region, with higher activity areas matched to lower activity areas. Each PHT's engagement in licensing for each 6 month period from April 2012 to March 2019 was quantified using a new measure (PHIAL) developed using structured interviews, documentary analyses, and expert consultation. Outcomes examined were ambulance callouts, alcohol-related hospital admissions, alcohol-related and alcohol-specific mortality and violent, sexual and public order offences. Timeseries were analysed using multivariable negative binomial mixed-effects models. Correlations were assessed between each outcome and 18-month average PHIAL score (primary metric), cumulative PHIAL scores and change in PHIAL scores. Additionally, 6-month lagged correlations were also assessed. Findings: There was no clear evidence of any associations between the primary exposure metric and the public health or crime outcomes examined, nor between cumulative PHIAL scores or change in PHIAL score and any outcomes. There were no significant associations in England or Scotland when analysed separately or between outcomes and lagged exposure metrics. Interpretation: There is no clear evidence that allocating PHT resources to engaging in alcohol licensing is associated with downstream reductions in alcohol-related health harms or crimes, in the short term or over a seven year follow-up period. Such engagement likely has benefits in shaping the licensing system to take account of health issues longer term, but as current systems cannot reduce alcohol availability or contain online sales, their potential benefits are somewhat constrained. Funding: The ExILEnS project is funded by the NIHR Public Health Research Programme (project number 15/129/11). The views expressed are those of the authors and not necessarily those of the NHS, the NIHR or the Department of Health.